Are forgotten memories literal experiences of absences? Episodic forgetting and metacognitive feelings (Acta Scientiarum. Human and Social Sciences, 2022)
Are occurrent states of forgetting literal experiences of absences? I situate this question within the debate on mental time travel (MTT) to understand whether these states can be explained as literal experiences of absent episodic memories. To frame my argument, I combine Barkasi and Rosen’s literal approach to MTT with Farennikova’s literal approach to the perception of absences, showing that both are built on the idea that for an experience to be literal it must afford an unmediated contact with the object that constitutes it. I test the idea that forgetting affords literal experiences of mnemonic absences by considering different views of absence perception and I evaluate whether the objections raised against Farennikova’s approach also apply to my exploratory idea. I show that, while the idea resists the objections that an advocate of a cognitive approach to mnemonic absences may raise, the same does not apply to those elaborated by advocates of a metacognitive approach. Even if conceiving of occurrent states of forgetting as literal experiences of mnemonic absences sounds appealing, this idea is misleading. Therefore, I suggest conceiving of occurrent states of forgetting as states with metacognitive features, which track the absence of episodic memories from awareness in an affectively mediated way